2021
DOI: 10.1007/s00406-021-01301-8
|View full text |Cite
|
Sign up to set email alerts
|

A symptom-based approach in predicting ECT outcome in depressed patients employing MADRS single items

Abstract: Establishing symptom-based predictors of electroconvulsive therapy (ECT) outcome seems promising, however, findings concerning the predictive value of distinct depressive symptoms or subtypes are limited; previous factor-analytic approaches based on the Montgomery–Åsberg Depression Rating Scale (MADRS) remained inconclusive, as proposed factors varied across samples. In this naturalistic study, we refrained from these previous factor-analytic approaches and examined the predictive value of MADRS single items a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Depressive symptoms are quite heterogeneous, which might not only explain that about 30% of patients do not respond adequately to treatment [ 1 , 43 ] but also underscores the need for a better understanding of the specific effects of a particular treatment on symptomatology. In a previous study, in which we chose a single-item rather than a factor-based approach, we observed that in particular affective symptoms, such as apparent and reported sadness and inability to feel, improved most over the course of ECT [ 10 ]. In the current sample, we observed significant improvements for all four MADRS symptom dimensions, of which changes in the dimensions of sadness, negative thoughts, and detachment were also associated with the observed change in rsFC between the amygdala and DLPFC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depressive symptoms are quite heterogeneous, which might not only explain that about 30% of patients do not respond adequately to treatment [ 1 , 43 ] but also underscores the need for a better understanding of the specific effects of a particular treatment on symptomatology. In a previous study, in which we chose a single-item rather than a factor-based approach, we observed that in particular affective symptoms, such as apparent and reported sadness and inability to feel, improved most over the course of ECT [ 10 ]. In the current sample, we observed significant improvements for all four MADRS symptom dimensions, of which changes in the dimensions of sadness, negative thoughts, and detachment were also associated with the observed change in rsFC between the amygdala and DLPFC.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that distinct antidepressant treatments have differential effects on specific symptom dimensions, with improvements in cognitive symptoms after a single sub-anaesthetic dose of ketamine [ 9 ], whereas ECT specifically reduced affective symptoms [ 10 ]. Other studies that examined the relationship between specific symptom dimensions and overall ECT response found that core symptoms such as depressed mood and anhedonia improved more with ECT than somatic or vegetative symptoms [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These screening tools and approaches can result in more timely diagnosis and intervention, such as psychosocial support and treatments, all with the goal of reducing the risk of psychological manifestations and suicidality, in hopes of improving the overall prognosis and quality of life in patients suffering from psoriasis. Table 1 [48][49][50][51][52][53][54] summarizes the current instruments available to assess depression and SIs in psoriasis patients.…”
Section: Psychological Assessment In Psoriasis Patientsmentioning
confidence: 99%
“…Overall, patients who remain in a depressive episode have a poorer prognosis for their medical condition and an increased use of health services [ 4 ]. In this context, a predictive clinical or biological marker of ECT outcome would be an opportunity to improve patient care and reduce the cost of depressive disorders for the community [ 5 ]. However, the search for a biological marker predicting the future failure or success of ECT remains highly challenging [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%